2010
DOI: 10.1248/bpb.33.1658
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Species Aminopeptidase N Structure on the Activity Screening of Aminopeptidase N Inhibitor

Abstract: Aminopeptidase N (APN, EC 3.4.11.2) is a type 2 transmembrane zinc-dependent metallopeptidase of the superfamily of gluzincins, 1,2) which forms a noncovalently bound homodimer on the cellular membrane. It has a conserved pentapeptide consensus sequence HEXXH representing a zinc binding motif in its extracellular metalloprotease domain. It expresses in many cells and tissues, including myeloids, fibroblasts, brain cells, hepatocytes, osteoclasts, endometrial cells, epithelial cells of the liver, kidney, intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…As shown in Figure 4, the inhibition constants (K i ) of compound 2 and Bestatin against APN from porcine kidney microsomes (L6007, Sigma) were 2.79 ± 0.32 lM and 3.37 ± 0.24 lM, respectively. 14,15 It confirmed that the inhibitory activity of compound 2 was indeed better than the control Bestatin.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 65%
See 1 more Smart Citation
“…As shown in Figure 4, the inhibition constants (K i ) of compound 2 and Bestatin against APN from porcine kidney microsomes (L6007, Sigma) were 2.79 ± 0.32 lM and 3.37 ± 0.24 lM, respectively. 14,15 It confirmed that the inhibitory activity of compound 2 was indeed better than the control Bestatin.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 65%
“…15 So here we also investigated the inhibitory activity of compound 2 to human APN expressed on ES-2 (human ovarian clear cell carcinoma cells) and HL-60 (human promyelocytic leukemia cells) which expressed high level of APN. As displayed in Figure 5, both Bestatin and compound 2 indicated dose-dependent inhibitory activities against ES-2 and HL-60 at the concentration range of 0.512-1600 lM.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…It is necessary to examine the APN inhibitory effects of the compounds. On one side, human APN is a membrane-binding protein, while porcine APN is a plasma soluble one, which means that they would have different conformation in the active sites [64]. Factually, in our laboratory, some compounds performed quite different inhibitory effects towards human APN and porcine APN, compared to bestatin as the positive control, respectively, while some performed quite similar results.…”
Section: Expert Opinionmentioning
confidence: 77%
“…In mouse xenograft models, the tumor size was significantly reduced by combining the CD13 inhibitor with reactive oxygen species (ROS)-inducing chemo/radiation therapy. 10) CD13 is a potential candidate for development of targeted anticancer drugs, and synthesis of CD13 inhibitors will be of great significance. A convenient and reliable method for detecting the suppressing effect of enzyme activity by the CD13 inhibitor would be useful for the study of CD13 inhibitors.…”
Section: Introductionmentioning
confidence: 99%